2010
DOI: 10.1016/j.jembe.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heat-shock responses between the hydrothermal vent shrimp Rimicaris exoculata and the related coastal shrimp Palaemonetes varians

Abstract: The deep-sea vent shrimp Rimicaris exoculata is believed to occur at the hot end of the hydrothermal biotope in order to provide essential elements to its epibiosis. Because it is found close to hot venting water, R. exoculata lives in a highly fluctuating environment where temperature (2-40°C in the swarms) can exceed its critical maximal temperature (33-38.5± 2°C). In order to understand how this vent shrimp copes with hyperthermia, we compared its molecular heat stress response following an acute but non-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 53 publications
5
38
1
Order By: Relevance
“…These results are consistent with previous studies demonstrating increased transcription of genes coding for heat-shock proteins in response to the effects of high hydrostatic pressure and/or low temperature [26,27,29]. Increases in hydrostatic pressure have long been known to affect protein folding, impacting quaternary, tertiary and secondary structure [63].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies demonstrating increased transcription of genes coding for heat-shock proteins in response to the effects of high hydrostatic pressure and/or low temperature [26,27,29]. Increases in hydrostatic pressure have long been known to affect protein folding, impacting quaternary, tertiary and secondary structure [63].…”
Section: Discussionsupporting
confidence: 92%
“…Results of this study confirm that the hsp70 (form 1) gene is responsive to acute hydrostatic pressure stress. The relative fold change of the hsp70 (form 1) gene shown in this study is lower, however, than observed in previous research in response to a large temperature shock (Cottin et al, 2010;Ravaux et al, 2012). The hsp70 (form 2) gene showed no changes in expression at any time points, thus in response to pressure stress alone, the gene remains constitutively expressed.…”
Section: Discussioncontrasting
confidence: 88%
“…In this study, significant increases in the transcription of four genes; narg, gapdh, hsp70 (form 1) and actin were recorded in both the head and abdomen of Palaemonetes varians at various time points from 0 to 24 h following exposure to an acute 2 h hydrostatic pressure treatment. A second hsp70 isoform, hsp70 (form 2), which has previously been characterised as non-inducible following a heat stress (Cottin et al, 2010), was not transcriptionally regulated at any of the time points. Furthermore, respiration rates of the shrimp showed similar patterns to that revealed by the expression of the genes described above.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Stress response mechanisms allow marine organisms to cope with unexpected or sharp fluctuations in one or several biotic or abiotic factors (Aruda et al 2011;Clark and Peck 2009;Cottin et al 2010;Huang et al 2011;Lockwood et al 2010). Depending on the extent and duration of the stress, organisms can recover, survive for a time with an impaired fitness, or die.…”
Section: Introductionmentioning
confidence: 99%